Teaching BNCC Competences Through Robotics Aiming the Development of Soft Skills - El Haddad, Laila Pereira; Campos, Luis Felipe Rodrigues de Brito; Pazelli, Tatiana F. P. A. Taveira (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
This article presents the role of the Red Dragons robotics team, from the Federal University of São Carlos (UFSCar), in the development and application of a robotics course based on the content of the BNCC, motivated by the need for a new teaching approach in Brazilian schools, given the unsatisfactory indexes about basic education in the country obtained through exams such as Pisa. This course was offered to public school students in the city of São Carlos during the first half of 2023, applying teaching methods that differ from the traditional approach by emphasizing the development of cognitive skills such as the affective and metacognitive areas. In addition, an evaluation method was created to assess the effectiveness of the model.